Contemporary Textualities: Tendencies and Styles in Latin American Narrative - Pérez Montañés, Amanda (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This review article establishes a series of reflections on the relations between Latin American literature and contemporary aesthetics, and the ways in which the specific artistic languages redimension the fictional statute and its critical potential. It also considers innovative perspectives that escape canonical narrative and traditional genre categorization by imposing new aesthetic expressions and themes in which the experience of textual or physical displacement is present. This paper explores a corpus of con- temporary narrative works whose creative practices and discursive procedures operate on the frontier of genre, languages and forms of expression.